Immunothrombosis and thromboinflammation in host defense and disease. (3rd April 2021) - Martinod, Kimberly; Deppermann, Carsten
Abstract: Platelets are increasingly being recognized for playing roles beyond thrombosis and hemostasis. Today we know that they mediate inflammation by direct interactions with innate immune cells or secretion of cytokines/chemokines. Here we review their interactions with neutrophils and monocytes/macrophages in infection and sepsis, stroke, myocardial infarction and venous thromboembolism. We discuss new roles for platelet surface receptors like GPVI or GPIb and also look at platelet contributions to the formation of neutrophil extracellular traps (NETs) as well as to deep vein thrombosis during infection, e.g. in COVID-19 patients.